(untitled) (Research, Society and Development, 2023)
In this article, we aim to provide researchers in the category inclusion of people with disabilities with a historical sequence about the Brazilian presidents and their actions linked to the theme, creating or extinguishing secretariats of inclusion. As a way of synthesizing and analyzing the material already produced on public policies that deal with the subject, we opted for a bibliographical study, with the support of documentary research. The bibliographical research was based on the theoretical productions of thinkers such as Mazzotta, Jannuzzi and Sassaki, who are references in matters related to the policy of inclusion of people with disabilities in Brazil; the documentary research was carried out through analysis of the management report of the Secretariat of Special Education - SEESP, according to the laws regulated in Brazil in relation to the policy of inclusion of people with disabilities and the documents officially published on the policy of inclusion in the website of the Ministry of Education and Culture – MEC. From the analyzed facts, we came to the conclusion that the inclusion of this conclusion in the government guidelines and structure strengthens the development of public inclusion policies. And, in the face of the recent setbacks, we need to stay strong together in defense of a society for all. We must not let any rights be lost.